Truth Claim dan Implikasinya terhadap Usaha Penciptaan Kohesi Damai Antarumat Beragama - Nur Hidayat Wakhid Udin (Islamica: Jurnal Studi Keislaman, 2016)
One of the sacred missions carried out by every religion is spreading harmony and peace. However, the facts show us that religious sentiment often creates disharmony among religious adherents and it also often leads to conflict and violence. This problem is caused by, among others, truth claim which sees other religions as false. The truth claim has been in fact one of the main terms promulgated by every religion towards its followers. Using qualitative approach, this article attempts to explain that every single religion in the world possesses its own distinctive doctrine about truth. The doctrine about truth has in fact led to two implications, namely the positive implication and the negative one. The truth claim would result in positive effect when it is viewed prudently and not understood blindly. It means that every religious adherent should realize the existence of â€œotherâ€ truth out of his/her belief. On the contrary, the truth claim would bring about negative impact when it is seen sightlessly and understood through one-sided view. This negative attitude would be an obstacle for every effort to create peaceful relation among interfaith adherents.